(3GdeMGSHI GdMchejIs - (3eMeO LeGd Ydj(B, (3gdGdjs ((3YeGf(B:s (3OGQ UaGA(B,s, 2002)
(3GdEWGQ GdacQj ddeMGSHI GdMchejI,GdehGRfI GdYGeI ddOhdI,GdfXGe GdeMGSHj GdMchej aj VhA GdJTQjYGJ GdCQOfjI,GdeYGdLI GdeMGSHjI ddEjQGOGJ hGdebHhVGJ GdCNQi,GdeYGdLI GdeMGSHjI ddfabGJ hGdeOahYGJ GdCNQi,GdeYGdLI GdeMGSHjI ddYedjGJ GdeJYdbI HGdMSGHGJ GdLGQjI GdeOjfI,GdeYGdLI GdeMGSHjI GdeJYdbI HGdMSGHGJ GdLGQjI GdOGFfI,GdeYGdLI GdeMGSHjI ddMSGHGJ GdfXGejI,GdJbGQjQ hGdMSGHGJ GdNJGejI GdMchejI,GdQbGHI GdeGdjI GdMchejIs
(3GdedGMb U(B.341 (3HHdjhZQGajG U(B.358s
Keywords: (3GdeMGSHI GdMchejIs